Efficacy of influenza-like illness screening outpatient department for COVID-19 at a high-volume center: Unlocking routine outpatient department - Bhawna Mattoo; Radhika Sarda; Arvind Kumar; Kaleem Fatima; Ravneet Kaur; Naveet Wig (Journal of Public Health and Primary Care, 2022)
Background: The impact of COVID-19 pandemic over nonessential health services has been massive. We initiated influenza-like illness (ILI) screening for resumption of outpatient services at a tertiary care center and this study attempted to gauge its efficacy in effectively pruning out COVID-19. Methods: We included all the patients who had visited for an outpatient department (OPD) appointment during the study period. Patient's details and ILI symptoms were noted. Patients were then followed up telephonically after 2 weeks. The telephonic follow-up was to ensure RT-PCR status and complaints of any newly developed ILI post-OPD visit (within the last 14 days). Results: Out of the 957 patients who were enrolled, 929 patients were successfully followed up telephonically after 14 days. Only 13 who were screened out as “possible ILI,” were either RT-PCR negative or did not follow-up with a confirmatory test. The telephonic follow-up to ensure RT-PCR status and complaints of any newly developed ILI post-OPD visit (within the last 14 days) was noted in the rest of the patients. Only one participant out of 957 screened, tested positive for COVID-19. Conclusion: The period in which the study was held, the national positivity rate was low (around 3%). Therefore, in a resource-limited country such as India, it is astute to restart the OPD services in the preexisting setup using basic precautions and a verbal questionnaire during the slope of the pandemic.